IMPLEMENTASI KEBIJAKAN TERHADAP ANGKUTAN ANTAR JEMPUT DALAM PROVINSI (TRAVEL) DI KOTA PEKANBARU - Nadyasari "; Chalid Sahuri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Travel Transportation in Province (AJDP), is one of a solution the Riau Province Government has to offer in mass land transportation. The AJDP transportation is predicted to decrease the number of illegal mass transportation vehicles that operating at Riau in general, and Pekanbaru in particular which regulated in Transportation Ministry Decree Number 35 year 2003 about concerning the execution of the transport of the streets with public transportation, article 24.The purpose of this research is to find out the implementation of the policy on AJDP transportation in Pekanbaru. This research used a qualitative method by looking for facts which later used to generate the conclusion. The analysis method of this research is using the descriptive analysis, which clearly described various factors related to the phenomenon, from obtained and complief data, then developed using relevant theories. The technique used for data collecting is interview and observation.The result of this research showed the implementation execution of Travel Transportation in Province (AJDP) on Pekanbaru City has not fully worked yet. It is caused by the increasing number of illegal mass transportation in Pekanbaru which has to do with the lack of communication between Transportation Department and the travel companies, the human resource, or incapable personnel in supervising, and the inconsistency from the officers in cracking down the illegal travel, and also a complicated bureaucracy to legalise the illegal transportation to be come an offical AJDP.Keywords: policy implementation, AJDP transportation, illegal travel